2020
DOI: 10.21203/rs.3.rs-17335/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between social capital and mental health among older people living with HIV: The Sichuan Older HIV-Infected Cohort Study (SOHICS)

Abstract: Background: Mental health problems are common among older people living with HIV and associated with poorer health outcomes. Social capital is an important determinant of mental health problems but under-studied in this population. This study investigated the association between social capital and mental health problems among older people living with HIV in China. Methods: The study was based on the baseline data of a cohort study investigating mental health among older people living with HIV in Sichuan, China… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Random intercept models were used to allow the intercept of the regression model to vary across factories, which could account for intracorrelated nested data. Multilevel logistic regression models are commonly used in studies using cluster sampling methods [ 26 ]. Univariate two-level logistic models were first used to assess the significance of the association between each of the background characteristics and the dependent variables.…”
Section: Methodsmentioning
confidence: 99%
“…Random intercept models were used to allow the intercept of the regression model to vary across factories, which could account for intracorrelated nested data. Multilevel logistic regression models are commonly used in studies using cluster sampling methods [ 26 ]. Univariate two-level logistic models were first used to assess the significance of the association between each of the background characteristics and the dependent variables.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to the ndings of cross-sectional studies [12,54], we found that stronger social support and lower perceived social stigma at baseline were protective factors for mental health problems. A study among Chinese PLWH also showed that family and social networks, and the trust/intensity of relationships with family members and others played important roles in mental wellbeing [55]. In addition, studies have shown that living in a trusting social environment with lower stigma toward PLWH alleviates daily stressors and protects against mental health problems [55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…A study among Chinese PLWH also showed that family and social networks, and the trust/intensity of relationships with family members and others played important roles in mental wellbeing [55]. In addition, studies have shown that living in a trusting social environment with lower stigma toward PLWH alleviates daily stressors and protects against mental health problems [55][56][57]. On the one hand, strategies to encourage and teach PLWH to communicate with their family/friends for support are needed [58].…”
Section: Discussionmentioning
confidence: 99%
“…To achieve health equity across the country, special attention should be given to those vulnerable areas, such as Southwest China, the most HIV-affected regions across the at-risk groups where, for example, the annual average number of new HIV infections in Sichuan and Yunnan had exceeded 3,000 (old HIV infections account for about 18%) from 2004 to 2016 [35,36]. Using a unique cohort of vulnerable populations in Southwest China, the Sichuan Old HIV-Infected Cohort Study (SOHICS) [37], this study was aimed at investigating the association between social capital and QoL among old PLWH. A previous study has revealed a positive association between social capital and mental health among this population [37].…”
Section: Introductionmentioning
confidence: 99%
“…Using a unique cohort of vulnerable populations in Southwest China, the Sichuan Old HIV-Infected Cohort Study (SOHICS) [37], this study was aimed at investigating the association between social capital and QoL among old PLWH. A previous study has revealed a positive association between social capital and mental health among this population [37]. Moving one step forward, the findings from this study would provide further information for the development of evidence-based interventions and policies for improving the QoL of old PLWH.…”
Section: Introductionmentioning
confidence: 99%